The The Role of Intellectual Performance Efficiency and its Components on Firm Performance: Moderating Effect of Innovation Capital - muzaroah, siti; subagyo, Herry; tristiarini, nila (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This article explains the influence of intellectual performance efficiency (MVAIC) and the moderating effect of innovation capital on company performance. The research population includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. This study used a purposive sampling method, and 18 companies meet the criteria, resulting in 108 observations. The MVAIC method was chosen because it encompasses RCE and INCE, and research on this topic in Indonesia is limited. Panel data regression was used for estimation, and Sequential Residual Centering (SRC) was applied to address multicollinearity. The study findings indicate that CEE, HCE, and SCE enhance profitability, while MVAIC, CEE, SCE, and RCE improve productivity. An important finding in this study is the moderating effect of INCE. INCE provides the appropriate environment and mechanisms to enable HC to effectively generate new ideas and improve ROA. Excessive investment in INCE can disrupt the optimization of the company's internal systems, processes, and infrastructure (SC), thereby affecting profitability. Excessive innovation priorities can divert resources from developing and maintaining strong external relationships (RC), thereby hindering productivity. The results of this study contribute to the understanding of potential trade-offs in IC investment, showing that excessive INCE can hinder financial performance derived from SC and RC. The implication, companies need to balance the allocation of IC resources to achieve holistic performance, rather than focusing solely on innovation.